ANALISIS KEPUASAN PELANGGAN TERHADAP LAYANAN PDAM TIRTA KHATULISTIWA PONTIANAK (Studi Kasus: Keluhan Para Pelanggan PDAM Tentang Kebutuhan Air Bersih Di Gang Harapan Kecamatan Pontianak Barat) - Salim Alqadrie, Syarifah Nadhilah; Genjik, Bambang; Okianna, Okianna (Universitas Tanjungpura, 2024)
The drinking water company is one of the companies that produces water services for the community, but in providing services to the community there are still many problems including the water quality which is said to be good. This study aims to determine how the quality of service and the efforts made by PDAM Tirta Khatulistiwa Pontianak. This research use desciptive qualitative approach. This research uses random sampling technique. Data collection techniques through observation, interviews and documentation. The results of this study indicate that the services provided by PDAM Tirta Khatulistiwa Pontianak cannot be said to be good because of the low water quality and responsiveness in responding to customer complaints. The problems that exist in PDAM Tirta Khatulistiwa Pontianak include the distribution of smelly water, where these problems become public complaints in the services of PDAM Tirta Khatulistiwa Pontianak. Therefore, in overcoming the problem of cloudy and mixed water distribution, PDAM Tirta Khatulistiwa Pontianak officers carry out supervision, routine checks correctly and evenly, thus creating good service quality.